Potential point-of-care microfluidic devices to diagnose iron deficiency anemia - Yap B.K.; Soair S.N.M.; Talik N.A.; Lim W.F.; Lai Mei I. (MDPI AG, 2023)
Fluidic devices; Iron; All-in-one; Blood-plasma separation; Iron deficiency; Micro fluidic applications; Micro-fluidic devices; Microfluidics devices; Point of care; Technological advancement; Microfluidics; human; iron deficiency anemia; lab on a chip; microfluidics; point of care system; Anemia, Iron-Deficiency; Humans; Lab-On-A-Chip Devices; Microfluidics; Point-of-Care Systems